Decentralised Governance Crafting Effective Democracies Around the World - Faguet, Jean-Paul; Pal, Sarmistha (LSE Press, 2023)
For developing countries, decentralising power from central government to local authorities holds the promise of deepening democracy, empowering citizens, improving public services and boosting economic growth. But the evidence on when and how decentralisation can bring these benefits has been mixed. Under the wrong conditions, decentralised power can be captured by unrepresentative elites or undermined by corruption and the clientelistic distribution of public resources. The picture is complex, and we still do not understand enough about what factors can contribute to creating better local government, and to what effect. Decentralised Governance brings together a new generation of political economy studies that explore these questions analytically, blending theoretical insights with empirical innovation. Individual chapters provide fresh evidence from around the world, including broad cross-country data as well as detailed studies of Bangladesh, India, Pakistan, China, Indonesia, Ghana, Kenya and Colombia. They investigate the pros and cons of decentralisation in both democratic and autocratic regimes, and the effects of critical factors such as advances in technology, citizen-based data systems, political entrepreneurship in ethnically diverse societies, and reforms aimed at improving transparency and monitoring. This wide-ranging volume examines the conditions under which devolving power can intensify democratic competition, boost transparency, and improve local governance, providing examples of good and bad practice in both. It is essential reading for researchers investigating decentralised governance, development and democratisation, and for policymakers and practitioners drawing lessons for future reforms.